Desejo, necessidade e realidade: os marcadores culturais e econômicos e suas implicações ocupacionais para o grupo profissional de engenheiros de produção no Brasil - Martins, Thais Joi (2015)
In order to seek answers to the changes currently taking place in the organization of work within companies, the modifications in the professional role of agents allocated in the organizational field and to understand the processes and dynamics that occur between social agents and this new organizational logic3 is that we will open space for the study of the cultural, economic and symbolic markers of life of the production engineers in the State of São Paulo. That is, from the study of their educational and vocational training, which results in their tastes and lifestyles and their different capitals, we seek to comprehend how the organizational dynamism in the 21th century and the relationship of a new "financial" operation engineer occur in contrast with the former acting "productive" occupied by the engineer. Will be analyzed to reflect on the actions and performances that occur within this professional group with regard. In other words, we if the desire to occupy a particular sector corresponds to the real occupation obtained by these engineers and what are the "driving" forces which will conduct their choicesWhat is the real occupation of these engineers currently and why? It is known among these professionals of the engineering that the options in the financial sectors are the most interesting because they are the entrance door to large financial gains and higher wages. Once given this statement, we can ask ourselves: do the choices of these engineers always give the sense of value for money or is there a different logic behind these choices? What is the real role of the economic, cultural and symbolic capital of these individuals in decision-making? The most appropriate methodology for the research is the bibliographical and prosopographical analysis, besides the multiple correspondence analyses inspired by Pierre Bourdieu. We will analyze, thus, through interviews and the usage of questionnaires to the students of Production Engineering from Federal University of São Carlos, from the Polytechnic University of São Paulo and from a private university. These methodologies will help us both qualitatively and quantitatively to delve deeper into the desired positions and the actual occupations of the production engineers, as well as into the relationship of these occupations with the economic, symbolic and cultural markers of each professional group studied. As a result, we found that there really is a homology between the symbolic capital of the agents and their statements when the direction of their professions. This social reproduction logic puts the Polytechnic University of São Paulo at the head of approaching the finance and consulting sectors. Place the Federal University of São Carlos in a secondary position as the symbolic capital counterparts in larger percentage of the choices in the industrial area and the private university studied the end of the hierarchy whose students do not even have the possibility of providing the selection processes in organizations in finance or consultants.